Characterization of the Pho89 phosphate transporter by functional hyperexpression in Saccharomyces cerevisiae - Zvyagilskaya, Renata A.; Lundh, Fredrik; Samyn, Dieter; Pattison-Granberg, Johanna; Mouillon, Jean-Marie; Popova, Yulia; Thevelein, Johan M.; Persson, Bengt L. (FEMS yeast research, 2008)
Abstract The Na+-coupled, high-affinity Pho89 plasma membrane phosphate transporter in Saccharomyces cerevisiae has so far been difficult to study because of its low activity and special properties. In this study, we have used a pho84Δ pho87Δ pho90Δ pho91Δ quadruple deletion strain of S. cerevisiae devoid of all transporter genes specific for inorganic phosphate, except for PHO89, to functionally characterize Pho89 under conditions where its expression is hyperstimulated. Under these conditions, the Pho89 protein is strongly upregulated and is the sole high-capacity phosphate transporter sustaining cellular acquisition of inorganic phosphate. Even if Pho89 is synthesized in cells grown at pH 4.5–8.0, the transporter is functionally active under alkaline conditions only, with a Km value reflecting high-affinity properties of the transporter and with a transport rate about 100-fold higher than that of the protein in a wild-type strain. Even under these hyperexpressive conditions, Pho89 is unable to sense and signal extracellular phosphate levels. In cells grown at pH 8.0, Pho89-mediated phosphate uptake at alkaline pH is cation-dependent with a strong activation by Na+ ions and sensitivity to carbonyl cyanide m-chlorophenylhydrazone. The contribution of H+- and Na+-coupled phosphate transport systems in wild-type cells grown at different pH values was quantified. The contribution of the Na+-coupled transport system to the total cellular phosphate uptake activity increases progressively with increasing pH.